Bilateral Optic Disc Edema as a Presentation of an Obstructing Spinal Plasmacytoma. Issue 2 (March 2016) - Grixti, Andre; Bonello, Michael; Silver, Nicholas; Noonan, Carmel; Ziahosseini, Kimia
Purpose: To report a rare case of bilateral optic disc edema as presentation of an obstructing spinal plasmacytoma. Methods: Case report. Results: A 41-year-old healthy man presented with distortion of his peripheral vision for 9 months. He denied headaches or neurologic symptoms. Examination showed bilateral optic disc swelling, radial disc hemorrhages, and absent spontaneous venous pulsations. Brain magnetic resonance imaging (MRI) and magnetic resonance venography were unrevealing. Lumbar puncture showed a normal opening pressure of 19 cm cerebrospinal fluid (CSF). CSF protein was significantly elevated at 3.22 g/L (0.10-0.45 g/L). Spinal MRI with contrast revealed a tumor in the T9 vertebral body extending through the disc spaces into T8 and T10, compressing the spinal cord. Computed tomography-guided biopsy confirmed a spinal plasmacytoma. He received radiotherapy to the spine T7-T11 to reduce spinal cord compression followed by a 6-month course of chemotherapy with dexamethasone, cyclophosphamide, and thalidomide. Disc swelling improved on starting radiotherapy with complete resolution 8 months posttreatment. MRI spine showed reduction of tumor. Conclusions: This case highlights the importance of spinal imaging in patients with normal cranial scans and raised CSF protein levels who lack the typical idiopathic intracranial hypertension phenotype.